Strategi Kepala Sekolah Untuk Meningkatkan Mutu Pendidikan - Salsabila Erliani; Ayu Putri Julia; Lilis Astika; Tamimi Mujahid; Rahmad Riadi Batubara; Rizki Akmalia (Simpati, 2023)
This article discusses the strategies or methods of school principals in improving the quality of education. Various ways are done so that the quality of education can be increased. So how to improve the quality of education in educational institutions? It is on this basis that this article was created in order to find out ways to improve the quality of education, starting from strategies, obstacles to solutions to overcome them. The research method used was in the form of an interview method in which data analysis techniques were used to describe each problem that triggered the students' lack of interest in reading. It can be concluded that improving the quality of education is quite a challenge for educational institutions. Because from there you can measure the level of educational stability in schools.